2008
DOI: 10.1002/pen.21116
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of poly(butylene terephthalate) wastes by blending with virgin polypropylene: Effect of the composition and the compatibilization

Abstract: Blends of recycled poly(butylene terephthalate) (PBT) parts obtained from scrapped cars, and virgin polypropylene (PP), were prepared in a twin‐screw extruder at different compositions. Selected compositions were also prepared with the presence of ethylene‐co‐glycidyl methacrylate copolymer (E‐GMA) and ethylene/methyl acrylate/glycidyl methacrylate terpolymer (E‐MA‐GMA) compatibilizers. The effect of the composition and the type of compatibilizer, as well as the mixing conditions, on the morphology phase, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
2
13
0
8
Order By: Relevance
“…As expected, PHB presented the lowest value of impact strength and elongation, whereas the PP/PHB blend without compatibilizer presented intermediary properties between those of pure PP and PHB. When any of the compatibilizers was incorporated, the impact strength and elongation of the ternary blends increased significantly when compared to the PP/PHB blend, which is a typical result found in the literature when an elastomeric compatibilizer is added to a mixture 4, 7, 9–11, 13, 16, 23, 39. This result could be due to toughening by addition of a material with elastomeric character and/or the occurrence of effective compatibilization.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…As expected, PHB presented the lowest value of impact strength and elongation, whereas the PP/PHB blend without compatibilizer presented intermediary properties between those of pure PP and PHB. When any of the compatibilizers was incorporated, the impact strength and elongation of the ternary blends increased significantly when compared to the PP/PHB blend, which is a typical result found in the literature when an elastomeric compatibilizer is added to a mixture 4, 7, 9–11, 13, 16, 23, 39. This result could be due to toughening by addition of a material with elastomeric character and/or the occurrence of effective compatibilization.…”
Section: Resultssupporting
confidence: 57%
“…The efficiency of P(E–MA) as a compatibilizer for the PP/PHB system could also be attributed to physical effects, and it was greater than PP–MAH, possibly because of the higher amount of functional groups contained in P(E–MA) (29 vs 2 wt %, see Table I). Transesterification reactions were unlikely to have occurred between acrylate and polyester as they are very slow kinetically and can be neglected unless long residence times or catalysts are employed 10, 14, 23. In fact, in a previous study of PBT/P(E–MA) blends, the authors could not find the existence of grafted PBT, which indicated the absence of a reaction in this system 48.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, their addition even weakens the mechanical properties (Li et al, 2010;Barhoumi et al, 2008). First, copolymers themselves offer little benefit to the strength and stiffness of polymer blends because they tend to be "soft" materials.…”
Section: Filler-polymer Compatiblizationmentioning
confidence: 99%